X-Ray Causes mRNA Transcripts Change to Enhance Orai2-Mediated Ca2+ Influx in Rat Brain Microvascular Endothelial Cells - Xu, Fangfang; Wang, Yang; Gao, Huiwen; Zhang, Xinchen; Hu, Yu; Han, Tingting; Shen, Bing; Zhang, Lesha; Wu, Qibing (Frontiers in Molecular Biosciences, 2021)
Background: Radiation-induced brain injury is a serious and treatment-limiting complication of brain radiation therapy. Although endothelial cell dysfunction plays a critical role in the development of this pathogenesis, the underlying molecular mechanisms remain elusive. Methods: Primary cultured rat brain microvascular endothelial cells (BMECs) were divided into five groups without or with exposure of x-rays delivered at 5 Gy or 20 Gy. For the irradiated groups, cells were continued to cultivate for 12 or 24 h after being irradiated. Then the mRNA libraries of each group were established and applied for next-generation sequencing. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses were conducted to analyze the sequencing results. Quantitative polymerase chain reaction, western blotting, cck8 assay and intracellular calcium concentration assays were conducted to analyze the role of Orai2-associated SOCE in x-ray induced cellular injury. Results: In total, 3005 transcripts in all the four x-ray–exposed groups of BMECs showed expression level changes compared with controls. With the dose of x-ray augment and the following cultured time extension, the numbers of differentially expressed genes (DEGs) increased significantly in BMECs. Venn diagrams identified 40 DEGs common to all four exposure groups. Functional pathway enrichment analyses indicated that those 40 DEGs were enriched in the calcium signaling pathway. Among those 40 DEGs, mRNA and protein expression levels of Orai2 were significantly upregulated for 24 h. Similarly, calcium influx via store-operated calcium entry, which is modulated by Orai2, was also significantly increased for 24 h in x-ray–exposed BMECs. Moreover, the change in SOCE was suppressed by btp-2, which is a non-selective inhibitor of Orai. Additionally, X-ray exposure induced a significant decrease of proliferation in BMECs in the dose- and time-dependent manner. Conclusion: These findings provide evidence for molecular mechanisms underlying BMECs dysfunction in development of radiation-induced brain injury and suggest new approaches for therapeutic targets.